Rapid Analysis of Aristolochic Acid Analogues in Traditional Chinese Patent Medicine by LC-MS/MS - Jing Liu; Yang Liu; Yingxue Wu; Zhong Dai; Shuangcheng Ma (Journal of Analytical Methods in Chemistry)
Aristolochic acids have been demonstrated to have renal toxicity, cause carcinogenesis, and may cause gene mutations. A series of risk control measurements have been adopted worldwide since 1990s. Some varieties of traditional Chinese medicine with high content of aristolochic acids have been banned in China. However, some species containing aristolochic acids in microscale are still in use. In recent years, with the continuous awareness of drug safety, the aristolochic acid analogues were generally considered to be of potential safety risks. Among these constituents, aristolochic acid I is still the one with most studies. Therefore, in addition to aristolochic acid I, it is necessary to establish an accurate and rapid method to determine other aristolochic acid analogues. LC-MS/MS methods based on multireaction monitoring mode was established to simultaneously determine 9 aristolochic acid analogues including 5 aristolochic acids and 4 aristolactams for the first time. Furthermore, the method was applied for Long dan Xie gan Pill, a traditional complex compound preparation with a long history for treatment of diseases including hepatochlic hygropyrexia, dizziness, tinnitus, and deafness. It has attracted widespread attention because of the aristolochic acid nephropathy. The crude drug Caulis Aristolochiae manshuriensis (Guanmutong) collected in the prescription was replaced by Akebiae Caulis (Mutong), and the established method helps to understand the product safety on market. As a result, aristolochic acid I, aristolochic acid Iva, and aristolactam I were detected and determined in one batch of Long dan Xie gan Pill among 25 batches of samples. It provided practical approach to demonstrate trace aristolochic acids and aristolactams. It was beneficial to control the safety of related traditional Chinese medicine products.